Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The reality of the use of artificial intelligence applications by students of the Faculty of Graduate Education at King Abdul-Aziz University in the light of some variablesHalima Hasan Alfageeh, Leena Ahmad Alfarani 2. Psychological well- being and its relationship to academic achievement at Sultan Qaboos University - Sultanate of OmanHilal Salem Suleiman Al-Abri 3. Psychological Vitality and its relationship to Emotional Blackmail in a Sample of Husbands who are Emotionally Separated from their WivesOmar Sulaiman Al-Shelash 4. Post-Stroke Death Anxiety of a Sample of Stroke Patients at Bethlehem Arab Society for Rehabilitation and SurgeryMirna Mario Kharoufeh, Ola Ali Hussein 5. Health behavior and its relationship to existential anxiety among a sample of health sector students During the Corona pandemicSarah Maflh Shaleh Alharthi 6. The impact of the psychological and social dimensions of digital transformation on the behavior of the individual and his family relations in the State of KuwaitFalah Saud Hasan Alrashidi 7. Attitudes of Arabic teachers towards distance learning in the schools within the green line in Palestine, and the obstacles that face them during any crisisShaheen Jameel Shayeb, Maysa Mahmoud Bsharat, Khitam Mohamed Nathan Saqer 8. The Role of Strategic Vigilance as an Entrance to Achieving the Strategic Leadership in Saudi UniversitiesSylvia Ismail Mohammad Bani Hani
Keywords: Journal of Educational and Psychological Sciences